The Role of Quality of Service as a Tool to Achieve Relationship Marketing. An Empirical Study of a Sample of Mobile Phone Company (Asiacell) Customers in Anbar Governorate - Tume Atua, Tarek; Lateef Dahham, Dahham; Salim Mesr, Ihsan (Opción, 2019)
The aim of the research is to demonstrate the possibility of determining the role of service quality as a tool to achieve marketing in the relationship, and the communication company (Asiacell) has been chosen as one of the organi- zations most practicing the contents of the service about that the variables and dimensions of the research are more clear and consistent and consistent with the specificity of the subject of the research, while the research sample was from Those who benefited from the services of the Asiacell communication company were formed from the owners of offices and sales representatives of the Asiacell communication company, and the number of individuals who were chosen and distributed to them was the research questionnaire (222) in- dividuals from the owners of offices and sales representatives, and the ques- tionnaire was used as a tool to collect information Available for personal inter- views to members of the sample died to prove the findings of the researchers from the results there is interest by the organization and the quality of service scheduling in its scope. It also seeks to build a solid relationship with custom- ers by providing the best services that are always described as the (strongest, fastest, highest). This confirms a logical conclusion on the existence of a cor- relation relationship and a significant effect between research variables and their dimensions.